Eksplorasi Udeng Pacul Gowang Sebagai Sumber Belajar Etnomatematika Di Sekolah Dasar - Fitrani, Nurokhmah; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
One of the interesting things about Sidoarjo Regency is the strong heritage of Majapahit culture, including traditional clothing. Part of the traditional clothing complement is the typical Sidoarjo Udeng Pacul Gowang. The aim of this research is to dig deeper into the history of udeng pakul gowang, study the aesthetics of the shape of udeng made by craftsmen, foster a sense of love for culture by instilling a sense of pride and love for local culture, and make mathematics learning more interesting for students by integrating udeng pacul gowang making in mathematics learning. In ethnomathematics, udeng pacul gowang is used as a learning resource that can be linked to mathematics subjects. The method used in this research is descriptive qualitative which focuses on understanding descriptions and interpretations in detail and emphasizes actual conditions without any manipulation. Data collection techniques with research are used to collect in-depth information from various sources, including through (1) interviews, (2) observation, and (3) documentation studies. The results of the research show that through the udeng pacul gowang learning resource, students can learn culture with various mathematical concepts including: counting concepts, algebra, geometry, measurement, and others. Thus, it is hoped that the government and schools will support the development of a curriculum based on local wisdom, so that students can learn mathematics in a context that is more relevant to their culture.